O самостоятельности вида Erodium sosnowskianum Fed. (Geraniaceae) - Р. Г. Адамян (ՀՀ ԳԱԱ հրատ.)
На основании дополнительного исследования макроморфологических признаков, включая признаки строения семени и плода, обоснована самостоятельность вида Erodium sosnowskianum Fed.The independence of the species Erodium sosnowskianum Fed. is confirmed on the additional reseаrch of macromorphological characteristics, including the characteristics of the structure of the seed and fruit. Erodium sosnowskianum Fed. տեսակի ինքնուրույնությունը հաստատվում է մակրոմորֆոլոգիական հատկանիշների լրացուցիչ հետազոտություններով` ներառյալ սերմի և պտղի կառուցվածքի հատկանիշները:
Keywords: Biology; Botany; Mycology